Defining intraspecific conservation units in the endemic Cuban Rock Iguanas (Cyclura nubila nubila) - Kyle J. Shaney (Nature Portfolio, 2020)
Abstract Defining conservation units is an important step in species management and requires interpretation of the genetic diversity and ecological function of the taxon being considered. We used the endemic Cuban Rock Iguanas (Cyclura nubila nubila) as a model to highlight this challenge and examined patterns of its intraspecific genetic diversity across Cuba. We evaluated nuclear (microsatellite loci) and mitochondrial diversity across eight populations from the island and its off-shore cays, and applied the population genetics results for assignment of Management Unit (MU) status and Evolutionary Significant Units (ESUs) based on phylogeographic and time of divergence information. We identified at least six distinct Cuban Rock Iguana MUs, encompassing demographically isolated and genetically differentiated populations across Cuba, most with low effective population size, declining populations, and with high risk of inbreeding and genetic drift. Hence, each MU should be considered of urgent conservation priority. Given the key ecological seed dispersal role of C. n. nubila, the disappearance of any MU could trigger the loss of local ecological functional diversity and major negative impacts on their ecosystems. Two divergent ESUs were also identified, exhibiting an historical east–west geographic separation on Cuba. Based on a Caribbean phylogeographic assessment, our findings strengthen the conclusion that all geographically and evolutionarily differentiated Cyclura species and subspecies across the archipelago warrant ESU distinction.